2020
DOI: 10.1017/s0022029919000980
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermented whey with a probiotic bacterium on gut immune system

Abstract: The aim of the work presented in this Research Communication was to evaluate the effect of fermented whey (FW) with Lactobacillus rhamnosus RC007 in a mice model. BALB/c mice were divided into three groups: control group: animals received orally 0.1 ml of phosphate buffered saline (PBS); FW group: animals received orally 0.1 ml of FW; whey (W) group: animals received orally 0.1 ml of W without fermentation with probiotic bacterium. After 10 d mice were sacrificed. Small intestines were collected for determinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Numerous in vivo studies have reported that many genera of probiotic Lactobacilli had protective effects on the gastric mucosa; the underlying mechanisms, however, remain to be fully elucidated [11][12][13][14][15][16]. Lactate is a major metabolite of Lactobacilli that has been widely used as a food additive for human [17,18]. Using different disease models, Hoque et al (2014) and Ranganathan et al (2018) both found that lactate was able to attenuate intestinal inflammation via endothelial lactate-receptor GPR81 signaling pathway [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous in vivo studies have reported that many genera of probiotic Lactobacilli had protective effects on the gastric mucosa; the underlying mechanisms, however, remain to be fully elucidated [11][12][13][14][15][16]. Lactate is a major metabolite of Lactobacilli that has been widely used as a food additive for human [17,18]. Using different disease models, Hoque et al (2014) and Ranganathan et al (2018) both found that lactate was able to attenuate intestinal inflammation via endothelial lactate-receptor GPR81 signaling pathway [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In pigs, probiotic supplementation increased the diversity of the microbiota and altered gene expression of key innate immune molecules and cytokines ( 36 ). A range of immunomodulatory effects of probiotics in the gut have also been described in mice ( 37 , 38 ). Interaction between probiotic strains and the gut immune system is recognized to be an important step in the mechanism linking probiotic supplementation to beneficial health effects.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports have demonstrated the beneficial effects of probiotics such as lactic acid bacteria and bifidobacteria [ 28 , 29 , 30 , 31 , 32 ]. In addition, many findings on the beneficial effects of whey derived from fermented milk have attracted attention [ 33 , 34 , 35 , 36 ]. In this study, we examined the effects of LHMW on melanogenesis with the aim of exploring a potential novel function of LHMW on the skin.…”
Section: Discussionmentioning
confidence: 99%